Evaluation of the Possibility to Detect Circulating Tumor DNA From Pituitary Adenoma - Megnis, Kaspars; Peculis, Raitis; Rovite, Vita; Laksa, Pola; Niedra, Helvijs; Balcere, Inga; Caune, Olivija; Breiksa, Austra; Nazarovs, Jurijs; Stukens, Janis; Konrade, Ilze; Pirags, Valdis; et al. (Frontiers in Endocrinology, 2019)
Objective: Circulating free DNA (cfDNA) in general and circulating tumor DNA (ctDNA) in particular is becoming an increasingly used form of liquid biopsy biomarkers. In this study, we are investigating the ability to detect ctDNA from the plasma of pituitary adenoma (PA) patients. Design: Tumor tissue samples were obtained from planed PA resections, before which blood plasma samples were taken. Somatic variants found in PA tissue samples were evaluated in related cfDNA, isolated from plasma samples. Methods: Sanger sequencing, as well as previously obtained whole-exome sequencing data, were used to evaluate somatic variants composition in tumor tissue samples. cfDNA was isolated from the same PA patients and competitive allele-specific TaqMan PCR and amplicon-based next-generation sequencing (NGS) approach were used for targeted detection of variants found in corresponding tumor tissue samples. Results: Using NGS-based analysis, we detected five out of 17 somatic variants in 40 to 60% of total reads, three variants in 0.50–5.00% of total read count, including GNAS c.601C>T, which was detected using ultra-deep NGS (1.78 million X) in 0.77% of amplicons reads. Nine variants were not detected. We also detected We were not able to detect variant found in PA tissue in cfDNA using cast-PCR, indicating that the portion of variant-containing ctDNA in total isolated cfDNA is too small to be detected with this method. Conclusions: For the first time, we demonstrate the possibility to detect somatic variants of PA in cfDNA isolated from patients' blood plasma. Whether the source of variant detected in cfDNA is PA should be further tested.